Determinants and disparities: A simulation approach to the case of child health care. (March 2015) - Lay-Yee, Roy; Milne, Barry; Davis, Peter; Pearson, Janet; McLay, Jessica
Abstract: Though there is much agreement on the importance of the social determinants of health, debate continues on suitable empirically-based models to underpin efforts to tackle health and health care disparities. We demonstrate an approach that uses a dynamic micro-simulation model of the early life course, based on longitudinal data from a New Zealand cohort of children born in 1977, and counterfactual reasoning applied to a range of outcomes. The focus is on health service use with a comparison to outcomes in non-health domains, namely educational attainment and antisocial behaviour. We show an application of the model to test scenarios based on modifying key determinants and assessing the impact on putative outcomes. We found that appreciable improvement was only effected by modifying multiple determinants; structural determinants were relatively more important than intermediary ones as potential policy levers; there was a social gradient of effect; and interventions bestowed the greatest benefit to the most disadvantaged groups with a corresponding reduction in disparities between the worst-off and the best-off. Our findings provide evidence on how public policy initiatives might be more effective acting broadly across sectors and across social groups, and thus make a real difference to the most disadvantaged. Highlights: Modifying social determinants of health is the key to reduction of disparities. We use a dynamic micro-simulation model of a New Zealand 1977 birth cohort. Positive impact is gained by improving multiple especially structural determinants. Social gradients exist with the most disadvantaged groups gaining most benefit. Findings support broad public policies that work across sectors and social groups.